2022
DOI: 10.1200/jco.2022.40.16_suppl.519
|View full text |Cite
|
Sign up to set email alerts
|

A randomized presurgical trial of alternative dosing of exemestane in postmenopausal women with early-stage ER-positive breast cancer.

Abstract: 519 Background: Successful therapeutic cancer prevention requires definition of the minimal effective dose of the proposed agent. Aromatase inhibitors substantially decreased breast cancer incidence in high risk postmenopausal women in phase III trials but their clinical use in prevention and adherence in adjuvant setting is limited by adverse events. We conducted a randomized presurgical phase IIb trial to evaluate two alternative doses of exemestane. Methods: We conducted a multi-center, pre-surgical, doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…48 In addition, new evidence suggests a lower dose of an AI is likely to be just as effective in lowering serum estradiol. 49 Limitations Our study has several limitations. First, the COVID-19 pandemic began during our data collection process, so results may be confounded by the public health crisis.…”
Section: Opportunitiesmentioning
confidence: 98%
“…48 In addition, new evidence suggests a lower dose of an AI is likely to be just as effective in lowering serum estradiol. 49 Limitations Our study has several limitations. First, the COVID-19 pandemic began during our data collection process, so results may be confounded by the public health crisis.…”
Section: Opportunitiesmentioning
confidence: 98%
“…To alleviate the unwanted side effects, low-dose exemestane trials are currently in progress. A recent phase IIb trial in postmenopausal women with early stage breast cancer demonstrated that exemestane given three days a week is not inferior to daily dosing [NCT02598557 ( 88 )]. Future comparison studies of low-dose exemestane and low-dose tamoxifen in the prevention setting are needed.…”
Section: Steroid Hormone Receptorsmentioning
confidence: 99%